2010
DOI: 10.2320/matertrans.m2010032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Welding Parameters on Weld Formation and Mechanical Properties in Dissimilar Al Alloy Joints by FSW

Abstract: The dissimilar Al alloys, 5052 and 5J32, were joined by friction stir welding (FSW) technique under several welding conditions, including material arrangement. The tool rotation speeds were 1000 and 1500 rpm, and the welding speeds were varied within the range from 100 to 400 mm/min. At a tool rotation speed of 1000 rpm, all joints with the 5052 on the advancing side exhibited better properties than those with the opposite arrangement. When the 5J32 was placed on the advancing side, defect-free welds were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 22 publications
0
15
0
2
Order By: Relevance
“…Furthermore, certain defects in the fusion welding process, such as pores or cracks, are attributed to the limitation of the weld ability of the aluminum alloy [4]. However, Friction Stir Welding (FSW) can achieve solid-state welding without filler materials, which effectively avoids cracks and porosity defects [5][6][7][8][9][10]. Scialpi et al successfully conducted ultra-micro-friction stir welding on 0.8 mm 2024-T3 and 6082-T6 sheets, and analyzed the mechanical properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, certain defects in the fusion welding process, such as pores or cracks, are attributed to the limitation of the weld ability of the aluminum alloy [4]. However, Friction Stir Welding (FSW) can achieve solid-state welding without filler materials, which effectively avoids cracks and porosity defects [5][6][7][8][9][10]. Scialpi et al successfully conducted ultra-micro-friction stir welding on 0.8 mm 2024-T3 and 6082-T6 sheets, and analyzed the mechanical properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have investigated microstructures of FSW. 48,49 Somasekharan & Murr 50 showed that after the friction welding of the Al6061 alloy to the magnesium alloys by moving from the Al6061 alloy metal base to the joint zone, the size of the alloy grains significantly is decreased. Moreira and his colleagues by investigating the microstructural behavior of the Al6061 and Al6082 alloys' joint concluded that due to the high strain after plastic deformation, resulting from the friction welding of these alloys, the joint zone was more susceptible for recrystallization than other areas.…”
Section: Microstructural Studiesmentioning
confidence: 99%
“…The recent studies on the FSW of aluminum alloy were mostly on the metal ow of the heterogeneous material 9) and its microstructure change, 10) and for the materials, on the butt joint and lap joint for plates with AA 5xxx 11,12) and 6xxx. 13) There are a few studies on the FSW joint for the 3D curvature shape.…”
Section: Introductionmentioning
confidence: 99%